2020
DOI: 10.21037/jtd.2019.12.94
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of red blood cell distribution width-standard deviation (RDW-SD) in patients operated on due to non-small cell lung cancer

Abstract: Background: The aim of the study was to determine a survival prognostic value of selected blood morphological rates of patients, operated on due to non-small cell lung cancer (NSCLC). Methods: The study was conducted on 532 patients, surgically treated due to NSCLC, in stages IA-IIIA, 174 females and 358 males, mean age 63.6 years (36-84 years) were included in the study. Blood parameters and clinical factors were included in statistical analysis, in order to determine potential prognostic values of red blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…[17][18][19]. RDW-SD ≥43 was negatively correlated with NSCLC survival [20]. Recent studies have found that stage I NSCLC with elevated RDW-SD had short PFS and OS, which was similarly con rmed in our current study [21,22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[17][18][19]. RDW-SD ≥43 was negatively correlated with NSCLC survival [20]. Recent studies have found that stage I NSCLC with elevated RDW-SD had short PFS and OS, which was similarly con rmed in our current study [21,22].…”
Section: Discussionsupporting
confidence: 88%
“…The previous study which included 1387 postoperative patients with stage I NSCLC indicated that lymphovascular invasion was an adverse factor for postoperative recurrence and death, and Mollberg et al and Mitchell et al similarly indicated that stage I lung cancer with positive lymphovascular invasion had a poor prognosis, which was in agreement with the results of our study [ 17 19 ]. RDW-SD ≥43 fl was negatively correlated with NSCLC survival [ 20 ]. Recent studies have found that stage I NSCLC with elevated RDW-SD had short PFS and OS, which was similarly confirmed in our current study [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that blood morphology indices, such as red blood cell distribution width (RDW) [6][7][8][9][10][11][12][13], neutrophil-to-lymphocyte ratio (NLR) [14][15][16][17][18][19], and platelet-to--lymphocyte ratio (PLR) [6,[19][20][21], may be prognostic factors in cancer patients. Such indices could be particularly useful for clinicians given that the majority are based on routinely performed laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…The red blood cell distribution width (RDW), including RDW-coefficient of variation (CV) and RDW-standard deviation (SD), as simple and widely available hematological indices, is easily acquired from a routine blood test and reflects the degree of heterogeneity of erythrocyte size [ 5 ]. Traditionally, RDW-CV is used to explore the cause of underlying anemia, especially for differential diagnosis of IDA [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%